Hierarchical architecture of neo-sex chromosomes and accelerated adaptive evolution in tortricid moths - Yang, Fangyuan; Cao, Li-Jun; Nguyen, Petr; Ma, Zhong-Zheng; Chen, Jin-Cui; Song, Wei; Wei, Shu-Jun (Genome Research, 2025)
Sex chromosomes can expand through fusion with autosomes, thereby acquiring unique evolutionary patterns. In butterflies and moths (Lepidoptera), these sex chromosome–autosome (SA) fusions occur relatively frequently, suggesting possible evolutionary advantages. Here, we investigated how SA fusion affects chromosome features and molecular evolution in leafroller moths (Lepidoptera: Tortricidae). Phylogenomic analysis showed that Tortricidae diverged ∼124 million years ago, accompanied by an SA fusion between the Merian elements M(20 + 17) and MZ. In contrast to partial autosomal fusions, the fused neo-Z Chromosome developed a hierarchical architecture, in which the three elements exhibit heterogeneous sequence features and evolutionary patterns. Specifically, the M17 part had a distinct base composition and chromatin domains. Unlike M20 and MZ, M17 was expressed at the same levels as autosomes in both sexes, compensating for the lost gene dosage in females. Concurrently, the SA fusion drove M17 as an evolutionary hotspot, accelerating the evolution of several genes related to ecological adaptation (e.g., ABCCs) and facilitating the divergence of closely related species, whereas the undercompensated M20 did not show such an effect. Thus, accelerated evolution under a novel pattern of dosage compensation may have favored the adaptive radiation of this group. This study demonstrates the association between a karyotype variant and adaptive evolution and explains the recurrent SA fusion in the Lepidoptera.